Insetos associados com corpos em decomposição na Região Cafeeira Andina Colombiana (2010)
In Colombia, mainly classic forensic medicine methods were used to clarify crimes until 2004. However, other disciplines, including forensic entomology, started to be considered only after the New Accusatory System introduction in Bogotá and the Coffee Region in 2005. In order to provide tools for obtaining evidentiary material elements in judicial trials, it is presented here the succession of insects throughout the decomposition process of an exposed carcass of Sus scrofa Linnaeus 1758 (Suidae) and the Occurrence Matrix of colonizing species. This process was evaluated under ambient conditions in the Andean rural area of the city of Pereira, in the Mundo Nuevo district, located in a pre-montane Wet Forest area, from October to November 2006. A sampling period of 27 days and 3198 individuals were collected. We found these colonizing species in the following stages of decomposition: Lucilia eximia (Wiedemann, 1819) fresh; Hemilucilia semidiaphana (Rondani, 1850), Oxelytrum discicolle (Brullé, 1840), and Cochliomyia macellaria (Fabricius 1775) bloated; Chrysomya albiceps (Wiedemann 1819), Compsomyiops verena (Walker, 1849), Ophyra aenescens (Wiedemann, 1830) and Musca domestica Linnaeus, 1758 active; Fannia sp. advanced and Stearibia nigriceps (Meigen, 1826) remains. This study provides support tools to define the Post Mortem Interval that may be used by experts from government institutions and laboratories officially accredited.